Confirmation of five nitrofuran metabolites including nifursol metabolite in meat and aquaculture products by liquid chromatography-tandem mass spectrometry: Validation according to European Union Decision 2002/657/EC. (16th April 2021) - Guichard, Pierre; Laurentie, Michel; Hurtaud-Pessel, Dominique; Verdon, Eric
Graphical abstract: Highlights: Confirmatory method for five nitrofuran metabolites including the nifursol metabolite. European Union Decision 2002/657/EC was used for the method validation. The new RPA adopted by the EU has been fully achieved through CCα below 0.1 µg.kg −1 . Sample preparation allows to detect only protein-bound residues from matrices. The method applies to the categories of meat and aquaculture products. Abstract: LC-MS/MS method for confirmation of nitrofuran metabolites in meat and aquaculture products, including the nifursol metabolite (DNSH), was developed. The nitrofuran metabolites investigated were as follows: 3-amino-2-oxazolidinone (AOZ), 3-amino-5-morpholinomethyl-2-oxazolidinone (AMOZ), 1-aminohydantoine (AHD), semicarbazide (SEM) and 3, 5-dinitrosalicylic acid hydrazide (DNSH). The sample preparation includes a washing step, allowing to analyze only the fraction of protein-bound residues. The final optimized recovery solvent for injection was found to be a mixture of ammonium acetate 2 mM/acetonitrile (60/40 ; v/v). Matrix effects and stability in biological matrix and standard solution for DNSH have been also carried out. Method performances were assessed using criteria of the Decision (EC) No 2002/657 and considering the proposed-for-adoption reference point for action (RPA) of 0.50 µg.kg −1 under Reg 1871/2019. Trueness ranged 86.5%–103.7% and precision ranged 2.0%–6.5% on intra-laboratory reproducibility conditions. Decision limit (CCα) ranged 0.028–0.182 μg.kg −1 and capability of detection limit (CCβ) ranged 0.032–0.233 µg.kg −1 .